Biofuels and the politics of land-use change: Tracing the interactions of discourse and place in European policy making - Palmer, JR (SAGE Publications, 2014)
Whilst transport biofuels have enjoyed strong political support in Europe for much of the past decade, concerns over their full impacts have an almost equally long history. Since 2008 these concerns have centred most intently upon the land-use change impacts of biofuel production, whereby increased demand for biofuels leads nonagricultural landscapes to be converted—either directly or indirectly—into agricultural ones. Amongst other things, biofuel-driven land-use change might potentially lead to significant emissions of greenhouse gases (GHG), losses of biodiversity, reduced ecosystem resilience, degradation of soil and water resources, declines in regional food security, or even land rights infringements through so-called ‘land-grabbing’. Political debates surrounding biofuel-driven land-use change in Europe have historically been restricted, however, to considerations of technical modelling work addressing the GHG emissions that might result from this process, thereby ignoring a wide range of alternative issues. Adopting a discursive-institutionalist perspective, this paper scrutinises two interrelated sets of dynamics pertaining to the handling of this political issue in Europe. First, it examines how the specific bureaucratic context of Brussels has itself been constitutive of the discursive practices used by policy makers to establish and retain control of the prevailing political conception of biofuel-driven land-use change. Second, it examines how these practices have inevitably led to what Scott terms a “narrowing of vision” in policy makers' approach to this problem, with concomitant implications for the role occupied by conceptions of ‘place’ in the policy process. In both instances the argument is made that such interactions exclude critical perspectives on what is at stake in the drive for biofuels from relevant policy-making procedures altogether. In light of these conclusions, I contend that future geographical analyses of environmental policy making writ large should pay greater attention to the interactions of discourse and place, particularly if they are to better understand the precise mechanisms through which political controversy is ultimately managed and settled in modern democratic contexts today.